2007
DOI: 10.1103/physrevb.76.035214
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent spectroscopy of deep levels in ZnO thin films

Abstract: Epitaxial ZnO͑0001͒ thin films have been grown by pulsed-laser deposition on a-Al 2 O 3 and investigated by deep level transient spectroscopy ͑DLTS͒ and by Fourier transform infrared photocurrent ͑FTIR-PC͒ spectroscopy in the midinfrared wavelength range. FTIR-PC spectra of undoped ZnO layers show several well-resolved spectral features between 100 and 500 meV due to transitions from deep defect states either to the conduction band or to the valence band. They include the commonly observed intrinsic deep defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
6
19
0
Order By: Relevance
“…A number of studies have reported electrical properties similar to our E 1 level in the recent publications. A few notable reports are the following: Frenzel et al 23 found an electron trap associated with Zn interstitials having an activation energy ͑trap concentration͒ of 0.32 eV ͑10 14 -10 16 21 reported a similar level at an energy of 0.29 eV, attributed to an oxygen vacancy. The following critical commentary can be made while comparing our E 1 level with the previously reported defect levels in ZnO: ͑i͒ the activation energy being a fingerprint of a trap level does not have consistency and ͑ii͒ no consensus has been found on the identification of the level.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported electrical properties similar to our E 1 level in the recent publications. A few notable reports are the following: Frenzel et al 23 found an electron trap associated with Zn interstitials having an activation energy ͑trap concentration͒ of 0.32 eV ͑10 14 -10 16 21 reported a similar level at an energy of 0.29 eV, attributed to an oxygen vacancy. The following critical commentary can be made while comparing our E 1 level with the previously reported defect levels in ZnO: ͑i͒ the activation energy being a fingerprint of a trap level does not have consistency and ͑ii͒ no consensus has been found on the identification of the level.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the level E 1 is identified as a charged impurity. Furthermore, the majority of the research groups have reported Zn-related electron traps ͑interstitials and antisites͒ in intrinsically n-type ZnO material exhibiting relatively shallower energy spectrum ͑0.22-0.32 eV͒, 11,12,17,22,25 we therefore, attribute the foresaid charged impurity with Zn. This argument is consistent with the theoretical calculations revealing that Zninterstitials are shallower than O-related defects ͑interstitials and antisites͒ in ZnO.…”
Section: -3mentioning
confidence: 90%
“…For example, a number of studies have reported still unstable electrical properties of an electron defect level in bulk ZnO so far and the consensus on its identification is yet to be made. Some of the reports discuss the issues as what follows: Frenzel et al 11 found an electron trap associated with Zn-interstitials having an activation energy ͑trap concentration͒ of 0.32 eV ͑10 14 cm −3 ͒ below the conduction band, Wenckstern et al…”
Section: Introductionmentioning
confidence: 99%
“…The realization of n -type conduction is very important for ZnO applications in optoelectronic devices, and there are reports on the electrical property of the first group element-doped ZnO thin-films [32-36]. Various techniques such as pulsed laser deposition [37,38], magnetron sputtering [39,40], and molecular beam epitaxy [41] have been used to deposit thin-films of ZnO. The sol-gel method [42] has been receiving increased attention because of its many advantages such as low cost, simple deposition procedure, easier composition control, low processing temperature, and easier fabrication of large area films.…”
Section: Introductionmentioning
confidence: 99%